2017
DOI: 10.1002/ceat.201600542
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Gas‐Solid Behavior in Fluidized Beds with Superfine Particles

Abstract: Fluidized beds are commercially utilized in gas‐solid contacting processes such as the fluid catalytic cracking (FCC) process. Attempts have been made for bubbling fluidized beds to enhance the gas exchange between the bubble phase and the emulsion phase as well as to increase bubble holdup. Low‐density superfine particles 5070S were selected with average diameters of about 10 μm. Unlike agglomerate particulate fluidization of superfine particles on which other researchers have reported, the smaller bubbles, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…For 7040S-R, the Sauter diameters before and under fluidization were 53 and 124 μm, respectively. The fluidized particles are aggregates of primary particles, and the agglomerate size is > 40 μm, similar to that for 5070S reported by Goshima et al [7].…”
Section: Properties Of Fluidized Particlessupporting
confidence: 87%
See 2 more Smart Citations
“…For 7040S-R, the Sauter diameters before and under fluidization were 53 and 124 μm, respectively. The fluidized particles are aggregates of primary particles, and the agglomerate size is > 40 μm, similar to that for 5070S reported by Goshima et al [7].…”
Section: Properties Of Fluidized Particlessupporting
confidence: 87%
“…( 7): The density of fluidized agglomerates with 5070S particle was determined to be 215 kg m -3 from Eqs. ( 3)-( 7) using the mode diameters of primary particle and agglomerate of 5070S, as described by Goshima et al [7], where the density of 5070S agglomerates was estimated as 248 kg m -3 . The density of fluidized agglomerates obtained by the current theoretical model agreed well with that obtained by the Wen-Yu equation using the minimum fluidization velocity.…”
Section: Properties Of Fluidized Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many industrial dispersions, such as emulsions, foams, and suspensions, contain surfactants, proteins, and colloidal particles 1–5. For a long time, the multiphase flow behavior in these systems has been a part of scientific research due to their application in many technological processes for food, pharmacology, or oil recovery 6–8.…”
Section: Introductionmentioning
confidence: 99%
“…Muller et al [5] studied the bubble bevavior in two-dimensional fluidized beds using the technology of particle image velocimety. Goshima et al [6] compared the difference of fluidization characteristics between silica nanoparticles and hollow borosilicate glass microparticles and they analyzed the influence of bubbles' sizes from gas exchange rate. Through experiments, Dong et al [7] found that if the decrease of the degree of electrification of granules results in the increase of gas bubble sizes.…”
Section: Introductionmentioning
confidence: 99%